DISTRIBUTION OF TRACE ELEMENTS IN GROWTH ZONES AND SECTORS OF SPODUMENE CRYSTALS (PASHKI DEPOSIT, NURISTAN, AFGHANISTAN) - M.A. Ivanov; N. Hamdard; S.G. Skublov; V.V. Smolensky (Минералогия)
Regular distribution of several trace elements in spodumene crystals of the Pashki pegmatite Li deposits in Afghanistan (Nuristan province) is analyzed using secondary ion mass spectrometry (SIMS). Twenty seven local analyses of 19 elements were carried out in spodumene samples of different generations taken from pegmatites during field works of 2023. We studied an early generation spodumene crystal from blocky spodumene-quartz-albite pegmatite and two late generation spodumene crystals including an euhedral crystal from a quartz core of pegmatite and a crystal extracted from a mineralized cavity together with quartz crystal, albite, and muscovite. It is found that the Fe, B, and Be content is significantly higher in the growth pyramid of the pinacoid face (010) than in the growth pyramid of the prism face (021). From early to late growth zones, the Be, B, Fe, and Mn content increases and the K, Rb and Ti content decreases. The heterogeneity of trace element composition of spodumene crystals thus mostly depends on their sectoriality, which is caused by different crystal chemical conditions of the incorporation of isomorphic trace elements into the mineral structure on faces parallel and perpendicular to the direction of pyroxene chains of Si–O tetrahedra along axis [001] rather than by their zonation. From early to late generations of spodumene, the content of most analyzed trace elements significantly decreases corresponding to the ideas about the change in the crystallization fractionation of elements during the evolution of the pegmatite process transiting from the closed to open physicochemical system.